Normally we charge $1.00 for this answer

Today, you can get it FOR FREE if you

g+1, Follow or Like, us

Show me how to post my homework

Just do my homework!

  • HTML tags will be transformed to conform to HTML standards.
  • Add rel="nofollow" to external links
Question
Submitted by lollyf13 on Wed, 2012-01-25 18:48
due date not specified
answered 2 time(s)
lollyf13 is willing to pay $5.00
lollyf13 bought 0 out of 1 answered question(s)
4 anonymous students showed interest

y=4x-9 y=x-3

y=4x-9 y=x-3

Answer
Submitted by shahimermaid on Wed, 2012-01-25 19:29
teacher rated 380 times
4.33684
price: $1.00

The answer is

body preview (34 words)

y=4x-9
xxxxx

x x xx xx

x = x -y
xxxxxxxxxxx 1 from x

9-3 xxxxx -y xxxxx
x x xx xx xx

6/3 x x

x x x

put in 2

x x x -3 = -1


Buy this answer

Answer
Submitted by Doctor on Tue, 2012-02-21 11:07
teacher rated 0 times
0
price: $0.00

Solution: x=2, y=-1 -- see attached plot

Take the second equation and solve it for x:

y = x - 3 <=> x = y + 3

Now put your solution into the first equation instead of x:

y = 4 x - 9 = 4 (y + 3) - 9 = 4 y + 12 - 9 = 4 y + 3

Solve y = 4 y + 3 for y:

y = 4 y + 3 <=> -3 y = 3 <=> y = -3/3 = -1

Now use y = -1 in x = y + 3:

x = y + 3 = x = -1 + 3 = 2

== PLEASE RATE ME! ==

Attachments: